The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2003
DOI: 10.1007/s11908-003-0016-8
|View full text |Cite
|
Sign up to set email alerts
|

Can enterococcal infections initiate sepsis syndrome?

Abstract: Enterococci are the third most common nosocomial bloodstream pathogen and frequently are the causative pathogen(s) of intra-abdominal, genitourinary, surgical wound, endovascular, or other serious infections. In addition to a diverse spectrum of intrinsic and acquired antimicrobial resistance mechanisms, some strains of enterococci exhibit numerous virulence factors that facilitate mucosal adherence, tissue invasiveness, endovascular attachment, and inflammation production. However, the opportunistic nature of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
10
0

Year Published

2004
2004
2016
2016

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 56 publications
0
10
0
Order By: Relevance
“…2 Despite the general notion that these organisms possess low virulence, enterococci are frequently the causative organism identified with catheter-associated urinary tract infections (UTIs) and infective endocarditis. Although the independent capability of this organism to cause sepsis has been questioned earlier, [3][4][5][6] recent reports have shown that Enterococcus faecalis infection can lead to severe sepsis or septic shock in immunocompromised patients, burn patients and thermally injured mice, by modulation of the host systemic inflammatory response. [7][8][9] Lipoteichoic acid (LTA) has been reported earlier as an enterococcal PAMP recognized by host TLR2 to induce a signaling cascade that culminates in the activation of transcription factors and induction of pro-inflammatory cytokine expression.…”
Section: Introductionmentioning
confidence: 99%
“…2 Despite the general notion that these organisms possess low virulence, enterococci are frequently the causative organism identified with catheter-associated urinary tract infections (UTIs) and infective endocarditis. Although the independent capability of this organism to cause sepsis has been questioned earlier, [3][4][5][6] recent reports have shown that Enterococcus faecalis infection can lead to severe sepsis or septic shock in immunocompromised patients, burn patients and thermally injured mice, by modulation of the host systemic inflammatory response. [7][8][9] Lipoteichoic acid (LTA) has been reported earlier as an enterococcal PAMP recognized by host TLR2 to induce a signaling cascade that culminates in the activation of transcription factors and induction of pro-inflammatory cytokine expression.…”
Section: Introductionmentioning
confidence: 99%
“…Despite being a commensal, Enterococcus faecalis is endowed with traits that make it an opportunistic pathogen, especially in immunocompromised hosts (1,2). Enterococci have emerged as a leading cause of antibiotic-resistant infections and now rank among the most common nosocomial pathogens infecting the bloodstream, surgical sites, and urinary tract (3,4).…”
mentioning
confidence: 99%
“…This bacterium is mainly responsible for bloodstream, urinary tract, and surgical site infections and endocarditis (32). Notably, E. faecalis seems to modulate the host systemic inflammatory response in mono-or polymicrobial infections, leading sometimes to severe sepsis or septic shock in immunocompromised patients (3,39). Several enterococcal virulence factors, such as lipoteichoic acid (6,64), aggregation substance, and enterococcal binding substance (56), have been implicated in the stimulation of the inflammatory response in vitro.…”
mentioning
confidence: 99%